1988
DOI: 10.1111/j.1365-2621.1988.tb09317.x
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Extraction of Carotene and Lutein from Leaf Protein Concentrates

Abstract: Supercritical fluid carbon dioxide was used to extract carotene and Iutein from leaf protein concentrate (LPC). Extractions were performed using pressures of lo-70 MPa at 40°C and CO2 flow rates of 5-6 L/min. Over 90% of the carotene contained in LPC was removed at extraction pressures in excess of 30 MPa. Removal of lutein from LPC required higher extraction pressures (70 MPa) and gas volumes to attain a 70% recovery level. Experimental results were rationalized with the aid of solubility parameter theory. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…The combined moisture and pressure effect have greatly enhanced the selectivity of carotene extraction in the sample mixture. The results obtained in this study agreed with the published literatures that pressure increased the extraction rate of carotene (Favati, King, Friedrich, & Eksins, 1988;Goto, Sato, & Hirose, 1993). By pre-extracting about 40% of the triglycerides with low carotene content at 10 MPa and 20 MPa, carotene has been retained and enriched in the latter fractions with average concentration of 3942 mg/kg and recovery of 90% (Fig.…”
Section: Carotenesupporting
confidence: 95%
“…The combined moisture and pressure effect have greatly enhanced the selectivity of carotene extraction in the sample mixture. The results obtained in this study agreed with the published literatures that pressure increased the extraction rate of carotene (Favati, King, Friedrich, & Eksins, 1988;Goto, Sato, & Hirose, 1993). By pre-extracting about 40% of the triglycerides with low carotene content at 10 MPa and 20 MPa, carotene has been retained and enriched in the latter fractions with average concentration of 3942 mg/kg and recovery of 90% (Fig.…”
Section: Carotenesupporting
confidence: 95%
“…Several studies demonstrated that lutein and zeaxanthin extractions in different materials were more sensitive to the extraction pressure than extraction temperature in the supercritical fluid extraction (Favati et al, 1988;Naranjo-Modad, Lpez-Mungua, Vilarem, Gaset, & Brzana, 2000;Careri et al, 2001;Montero et al, 2005) On the other hand, extraction pressure was a major parameter for lutein and zeaxanthin extractions. Our results are in agreement with previous studies that extraction pressure was the most important parameter for lutein and zeaxanthin extraction from daylily flowers in SFE-CO 2 .…”
Section: Optimisation Of Extraction Conditionsmentioning
confidence: 99%
“…Previous studies on the extraction of carotenoids with SFE-CO 2 have focused mostly on extracting b-carotene and lycopene from carrots (Barth, Zhou, Kute, & Rosenthal, 1995), ripe tomatoes (Cadoni, Giorgi, Medda, & Poma, 2000) and watermelons (Katherine, Edgar, Jerry, Luke, & Julie, 2008). Favati, King, Friedrich, and Eskins (1988) investigated the SFE-CO 2 extraction of lutein from leaf protein concentrate at 40°C under six pressures ranging from 10 to 70 MPa. They reported that over 90% of the carotene from leaf protein concentrate was removed at extraction pressures in excess of 30 MPa, but the removal of lutein from the leaf protein concentrate required a higher extraction pressure of 70 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, carotenoids, mainly b-carotene, are widely used by the food, pharmaceutical, and cosmetic industries. Increasing demand for b-carotene, mostly natural b-carotene, has resulted in growing interest in extracting b-carotene from dierent natural sources (Vega et al, 1996) such as vegetable and fruit wastes (Favati et al, 1988;Keat et al, 1991;Sadler et al, 1990;Spanos et al, 1993;Vega et al, 1996). However, by far the highest concentrations of b-carotene are found in the halotolerant microalga Dunaliella salina, reaching levels of up to 100 g kg )1 on a dry weight basis (Ben-Amotz, 1993).…”
Section: Introductionmentioning
confidence: 97%